Performance of a tetramethylammonium fluoride tetrahydrate coated piezoelectric crystal for carbon dioxide detection - Gomes, MTSR
A coated quartz crystal microbalance is used for the determination of carbon dioxide. Coating of crystals with tetramethylammonium fluoride tetrahydrate is reported for the first time, and its behaviour, in terms of CO2 interaction at different temperatures, is discussed. This new coating gives greater stability to the calibration curve than N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine but less sensitivity for carbon dioxide, especially at higher CO2 concentrations.